2020
DOI: 10.1017/rdc.2020.45
|View full text |Cite
|
Sign up to set email alerts
|

Human Dietary Complexity in Tianshan Region and the Influence of Climate on Human Paleodiet

Abstract: With the popularization of carbon and nitrogen stable-isotope analysis methods used on archaeological samples from Xinjiang, the ancient paleodiet there has been revealed. However, research about isotopic analysis combined with environmental factors is rare, especially in such a variable and complex climate as that of the Tianshan region. We systematically analyzed the δ13C and δ15N results from animals and humans for dietary reconstruction of nomadic pastoralists from the Tianshan region during 3900–1200 cal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In addition to lacquer fragments, potteries and iron products, an array of gold and silver ornaments was found (Xinjiang Cultural Relics and Archaeology Institute, 2009). An isotopic analysis of animal and human bones found at Dongheigou suggested that the tomb occupants had been a group of people engaged in mobile herding economies subsidized with crops and wild animal meat in the Tianshan Mountains (Zhao & Zhou, 2020). The radiocarbon results suggest that while both the tomb's occupant and the human sacrifice in Tomb 12 can confidently be dated to the fourth to the second centuries bce (Figure 2) (see also Supplementary Material 01: Table S1 in the additional supporting information), the charcoals from early settlements in this archaeological site could be dated to as early as the eleventh century bce (Xinjiang Cultural Relics and Archaeology Institute, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to lacquer fragments, potteries and iron products, an array of gold and silver ornaments was found (Xinjiang Cultural Relics and Archaeology Institute, 2009). An isotopic analysis of animal and human bones found at Dongheigou suggested that the tomb occupants had been a group of people engaged in mobile herding economies subsidized with crops and wild animal meat in the Tianshan Mountains (Zhao & Zhou, 2020). The radiocarbon results suggest that while both the tomb's occupant and the human sacrifice in Tomb 12 can confidently be dated to the fourth to the second centuries bce (Figure 2) (see also Supplementary Material 01: Table S1 in the additional supporting information), the charcoals from early settlements in this archaeological site could be dated to as early as the eleventh century bce (Xinjiang Cultural Relics and Archaeology Institute, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The mountains run east–west, starting from Uzbekistan in the west and extending to Kyrgyzstan and northwestern China and southwestern Mongolia in the east, with a total length of about 2500 km, it is the largest independent latitudinal mountain system in the world 25 , 26 . The study area is the Tianshan Mountains in China region (Tianshan region, Xinjiang, China) 27 , 28 , located in the hinterland of the Xinjiang Uygur Autonomous Region, west to Yili Prefecture, east to Hami City, north to Bo Prefecture, and south to Aksu Region, Geographic location is 79E–96E, 41N–45N, with an area of 237,253.21 km 2 . The Tianshan region (study area) accounts for two-thirds of the length of The Tianshan Mountains and is about 1700 km long and 350 km wide 29 .…”
Section: Study Areamentioning
confidence: 99%
“…Understanding these early pastoral societies and their economy is, therefore, particularly important for the study of late Eurasian prehistory.Zooarchaeological research in Xinjiang has provided a window into the subsistence strategies and herd management of pastoralist and agro-pastoralist groups, who appear to have relied on the husbandry of a suite of animals, including cattle, horses, sheep, goats and dogs 12,13 . A growing corpus of isotopes and dental pathology analyses has enhanced our knowledge of domestication and ancient diets [14][15][16][17] . These methods have shown that by the first millennium BCE domesticated bovids were ubiquitously exploited to varying degrees of intensity in Northwest China.…”
mentioning
confidence: 99%